Alzheimer's Disease Biomarkers and Epigenetic Intermediates Following Exposure to Pb In Vitro - Waseem Bihaqi, Syed; H. Zawia, Nasser (Current Alzheimer Research, 2012)
Late onset Alzheimer's disease (LOAD) is typical of the majority of Alzheimer's disease (AD) cases (∼90%), and has no clear genetic association. Previous studies from our lab suggest that an epigenetic component could be involved. Developmental exposure of primates and rodents to lead (Pb) predetermined the expression of AD-related genes, such as the amyloid-β precursor protein (AβPP), later in life. In addition to AβPP, the preponderance of genes that were reprogrammed was rich in CpG dinucleotides implicating DNA methylation and chromatin restructuring in their regulation. To examine the involvement of epigenetic intermediates in Pb-induced alterations in gene expression, differentiated SH-SY5Y cells were exposed to a series of Pb concentrations (5-100 μM) for 48 h and were analyzed for the protein expression of AβPP, β-site amyloid precursor protein cleaving enzyme 1 (BACE1), specificity protein 1 and 3 (Sp1, Sp3) and epigenetic intermediates like DNA methyltransferase 1, 3a (Dnmt1, Dnmt3a) and methyl CpG binding protein 2 (MeCP2) involved in DNA methylation six days after the exposure had ceased. Western blot analysis indicated a significant latent elevation in AD biomarkers as well as the transcription factors Sp1 and Sp3, accompanied by a significant reduction in the protein levels of DNA methylating enzymes. RT-PCR analysis of Dnmt1, Dnmt3a and MeCP2 indicated a significant down-regulation of the mRNA levels. These data suggest that Pb interferes with DNA methylating capacity in these cells, thus altering the expression of AD-related genes.
Keywords: SH-SY5Y cells